Specific courts and tribunal - Ali Mohamed, Ashgar Ali (The Malaysian Current Law Journal Sdn Bhd, 2014)
Apart from the ordinary courts of law there are many courts with limited and specialised jurisdiction in Malaysia. Special courts usually do not follow the same procedural rules as in the courts of general jurisdiction. Further, special courts often proceed without the benefit or expense of legal representation. The judges who serve in the special courts are as varied as the special courts themselves. More importantly, cases are more likely to be disposed of speedily than in a court of general jurisdiction. Apart from the special courts, there are also many tribunals established in Malaysia. Although tribunals may resemble courts as they make a decision on a particular dispute, they are not part of the court system but run parallel to the court system. This chapter discusses the jurisdiction and powers of the selected special courts namely, the Syariah Court, Industrial Court, ‘Labour Court’ and Native Courts. Besides the special court, the chapter also includes the discussion of the selected tribunals namely, the Tribunal for Consumer Claims and the Tribunal for Homebuyer Claims